Genetic diversity of milk protein beta-lactoglobulin and association with production traits genomic values among Holstein cattle - MORKÛNIENË, K; MICEIKIENË, I; KERZIENË, S; BIZIENË, R; MISEIKIENË, R (The Indian Journal of Animal Sciences, 2018)
The aim of the study was to evaluate the prevalence of beta-lactoglobulin genotypes in Lithuanian Holstein dairy cattle population and to identify possible synergies between the different genotypes of beta-lactoglobulin and genomically predicted values for milk production traits. DNA samples were collected from Holstein cattle (147) and bovine beta-lactoglobulin gene polymorphism study was performed by PCR-RFLP method. A allele was identified with frequency 0.456, B allele, which can be used to carry out selection to improve milk processing properties, was found with 0.544 frequency. Three genotypes, viz. AA, AB, BB at different frequencies were identified. The biggest influence on the milk processing properties having BB genotype was found in 27.3% of the cows. Beta-lactoglobulin AA genotype cows had higher average genomic values for milk yield, while BB genotype cows had higher average genomic values for milk protein percentage, the differences have found statistically significant. Dispersion analysis showed that beta-lactoglobulin genotype influences 8.4% of milk amount genetic variation, 1.2% of milk protein amount genetic variation and 20.6% of milk protein percent genetic variation. Lithuanian Holstein cows population had higher average genomic prediction values for milk yield, milk protein amount and milk percentage than average genomic values of Igenity reference animal group. The existence of the most important genotype BB of beta-lactoglobulin for milk manufacturing properties, in studied population increases the possibility of selecting cows according to milk protein polymorphism, and could be economically important selection criteria for dairy herds designated for industrial milk production.